Bacterial consortia mediated induction of systemic tolerance to arsenic toxicity via expression of stress responsive antioxidant genes in Oryza sativa L. (January 2023) - Pandey, Neha; Xalxo, Roseline; Chandra, Jipsi; Keshavkant, S.
Abstract: Arsenic (As) is a toxic metalloid which pollutes soil and water, and negatively affects the growth and development of plants at different levels. This study investigated the effects of As-resistant and plant growth promoting (PGP) bacterial consortia on the germination and growth attributes of two cultivars (Swarna and MTU 1010) of rice ( Oryza sativa L.) under As-flooded environment. The consortium consisted of five bacterial strains; Bacillus nealsonii strain ARP2, Pseudomonas nitritireducens strain ARP3, Exiguobacterium aestuarii strain ARRP3, Bacillus tequilensis strain ART2 and Microbacterium paraoxydans strain ADT5, which were isolated from different regions of Chhattisgarh, India. Soils inoculated with the bacterial consortia and supplemented with As(V)/As(III) were used to grow rice seeds under in vitro conditions. The results ascertained that the seedlings inoculated with the bacterial consortia grew well even in the presence of As, which was marked by increased shoot and root length, biomass, and total chlorophyll content. Further, inoculation of bacterial consortia reduced the oxidative stress to a significant level by up-regulating the expressions of protective genes encoding antioxidant enzymes. This consortium could decrease the As accumulation in plants upon successful colonization in the rhizosphere, suggesting possible exploitation of it for enhanced growth of plants and in the remediation of As-contaminated soils. Graphical abstract: Image 1 Highlights: Inoculation with five bacterial consortium alleviated the toxic effects of As in Oryza sativa L. Presence of bacterial strains in the soil limit the uptake of As in seedlings. Bacterial strains successfully colonized the root surface of plants. Up-regulation of the expressions of protective genes encoding antioxidant enzymes was observed. Application of As-resistant PGP bacterial consortium can improve productivity and nutritional values.